2013
DOI: 10.1097/01.nna.0000435145.39337.d5
|View full text |Cite
|
Sign up to set email alerts
|

Lower Mortality in Magnet Hospitals

Abstract: Background Although there is evidence that hospitals recognized for nursing excellence—Magnet hospitals—are successful in attracting and retaining nurses, it is uncertain whether Magnet recognition is associated with better patient outcomes than non-Magnets, and if so why. Objectives To determine whether Magnet hospitals have lower risk-adjusted mortality and failure-to-rescue compared with non-Magnet hospitals, and to determine the most likely explanations. Method and Study Design Analysis of linked patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The results of previous studies have indicated that attention should be paid to professional interactions (McGlynn, Griffin, Donahue, & Fitzpatrick, 2012), and our data seem to suggest that the introduction of PN can improve the team climate, which can eventually increase job satisfaction. These results appear to be of paramount importance because good staff-related outcomes can also bring about positive changes in patient outcomes (Aiken et al, 2011;McHugh et al, 2013), and job satisfaction is a critical factor that indicates nurses' intention to leave (Chan, Tam, Lung, Wong, & Chau, 2013). Furthermore, a previous Cochrane review (Butler et al, 2011) indicated that PN may reduce staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies have indicated that attention should be paid to professional interactions (McGlynn, Griffin, Donahue, & Fitzpatrick, 2012), and our data seem to suggest that the introduction of PN can improve the team climate, which can eventually increase job satisfaction. These results appear to be of paramount importance because good staff-related outcomes can also bring about positive changes in patient outcomes (Aiken et al, 2011;McHugh et al, 2013), and job satisfaction is a critical factor that indicates nurses' intention to leave (Chan, Tam, Lung, Wong, & Chau, 2013). Furthermore, a previous Cochrane review (Butler et al, 2011) indicated that PN may reduce staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, we used hospitals with a minimum of 10 nurse respondents. Previous research has shown that having at least 10 nurse respondents per hospital provides an accurate summary of nurse-sensitive hospital features [ 1 , 39 , 40 ] and our study sample had, on average, 39 nurses per hospital, further minimizing our concern for bias in these measures. Additionally, this is the first study, to the authors’ knowledge, examining the impact of the work environment and Magnet status on the relationship between nurse burnout and patient outcomes, providing greater context for the interpretation of results in addition to highlighting solutions for hospital leaders.…”
Section: Discussionmentioning
confidence: 99%
“…The analytic sample included 20,496 nurses across 523 nonfederal, acute care hospitals from California, Pennsylvania, Florida, and New Jersey, of which 83 were Magnet hospitals. Consistent with previous empirical work, hospitals were included if they had at least 10 nurse respondents to aggregate individual reports of nurse burnout and the work environment to the hospital level [ 39 , 40 ]. In total, the patient sample included 1,939,878 surgical in-patients aged 18–99.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large proportion of less experienced nurses aged 31 or less at the BSN-education level in our sample likely reflects the demographics of hospitals with nursing accreditation. (McHugh et al 2013) Hospitals face unique retention challenges with new to practice nurses. Newly licensed registered nurses with an average age of 27 who experience coworker incivility reported poorer mental health (Laschinger et al 2013).…”
Section: Discussion and Implications For Nursing Managementmentioning
confidence: 99%